(untitled) (Caleidoscopio. Revista de Italianistica de ADILLI, 2026)
The Italian-language press in Argentina has historically functioned as a key site for the articulation of social, ideological, and political tensions within the emigrant community. Cultural content disseminated by periodicals played an active role in shaping ideological orientations, operating as a form of symbolic production and a vehicle for consensus-building through entertainment. During the Ventennio, following years of competition for hegemony over patriotic sentiment among Italians in the Río de la Plata region, the PNF delegate in Argentina, Vittorio Valdani, promoted the establishment of a new Fascist daily, «Il Mattino d’Italia». This article examines the cultural phenomena featured in this newspaper during the 1930–1931 biennium in order to assess their role within the regime’s strategy of symbolic legitimation and the patriotic rhetoric imposed on the Italo-Argentine community.